2006
DOI: 10.1002/hed.20526
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of recurrent nodal disease after definitive radiation therapy for nasopharyngeal carcinoma: Diagnostic value of fine‐needle aspiration cytology and CT scan

Abstract: Radiological imaging and FNAC are useful diagnostic modalities in assessing recurrent nodal disease in the post-irradiated neck in patients with NPC. Although routine CT scan criteria for pathologic lymphadenopathy cannot be accurately applied in the post-irradiated neck, it is a useful surveillance tool in the routine follow-up of patients with post-irradiated neck with NPC. Clinicians, however, must understand their limitations when assessing these patients. The possibility of negative neck dissection must b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 15 publications
(37 reference statements)
1
24
0
Order By: Relevance
“…In our previously published study on recurrent nodal disease, CT scanning had a positive predictive value of 78.6 per cent and a negative predictive value of 20 per cent for multilevel lymph node involvement. 12 The final pathological neck dissection specimen showed more nodal involvement than was radiologically evident. 12 These findings mirror reports by other investigators.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In our previously published study on recurrent nodal disease, CT scanning had a positive predictive value of 78.6 per cent and a negative predictive value of 20 per cent for multilevel lymph node involvement. 12 The final pathological neck dissection specimen showed more nodal involvement than was radiologically evident. 12 These findings mirror reports by other investigators.…”
Section: Discussionmentioning
confidence: 92%
“…12 The final pathological neck dissection specimen showed more nodal involvement than was radiologically evident. 12 These findings mirror reports by other investigators. 6,9,16,17 High resolution ultrasound (US) is reported to be more sensitive than clinical examination (92 per cent versus 70 per cent) in detecting and differentiating benign from malignant nodes.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…33 A study from Singapore found a higher PPV and NPV for US over CT in the evaluation of recurrent nodal adenopathy from nasopharyngeal cancer. 34 However, legitimate concerns have been raised about performance of US of the neck after RT as an inaccurate and overly formidable technical undertaking. One common belief is that fibrosis in the neck limits examination and makes FNAC samples overly difficult to obtain, and another is that either due to sampling error or idiosyncratically responding nodes at varying stages of posttreatment viability, reliable results are unlikely.…”
Section: Discussionmentioning
confidence: 99%